A negative heritage. The Orthodox cathedral at the Saski Square in Warsaw - Hołda, Renata (A mosaic city: The culture-oriented description, 2023)
The article is devoted to a historical, now non-existent building: the Orthodox cathedral of Saint Alexander Nevsky, which the Russians built in Warsaw’s Saski Square in the years 1894–1912. I treat this initiative as one of spatial practices aimed at demonstrating power and symbolically marking the subordinated space. I argue that the Russian initiators and builders of the cathedral treated this object instrumentally, as an opportunity to mark their dominance. This meant that in the new political reality, after Poland had regained its independence, the building was considered a negative heritage and was ultimately demolished.